Pincer cobalt complex-catalyzed Z-selective hydrosilylation of terminal alkynes. Issue 8 (10th May 2017) - Du, Xiaoyong; Hou, Wenjun; Zhang, Yanlu; Huang, Zheng
Abstract : Co-Catalyzed Z -selective hydrosilylation of terminal alkynes produces ( Z )-β-vinylsilanes, which are further converted to ( Z )-disubstituted alkenes by Pd-catalyzed cross couplings. Abstract : A phosphine-iminopyridine (P C NN) cobalt-catalyzed Z -selective hydrosilylation of terminal alkynes with Ph2 SiH2 has been developed for the synthesis of ( Z )-β-vinylsilanes with high regio- and stereoselectivity and wide functional group tolerance. Furthermore, the Co-catalyzed hydrosilylations of unsymmetrical arylalkyl disubstituted internal alkynes afford syn -addition products with unique regioselectivity: the silyl group is added to the alkyl-substituted carbon, instead of the aryl-substituted carbon. The ( Z )-β-vinylsilane products are further applied to Pd-catalyzed Hiyama–Denmark cross-couplings for stereoselective synthesis of ( Z )-disubstituted alkenes.